Analysis of Business Prospects for Aglonema Type Ornamental Plants in Mataram City - Iis Apriany, Baiq; Herdiana, Herdiana; Inggar Linggarweni, Baiq (International Journal of Sharia Business Management, 2023)
Aglaonema ornamental plant is one of the plants originating from Southeast Asia, is an ornamental plant known as sri fortune, which is an ornamental plant with the scientific name Aglaonema, sp, of which several varieties originate from Indonesia. Aglaonema comes from the Greek, namely aglos which means light and Nema which means thread. Literally aglaonema means shining thread. Aglaonema is one of the ornamental plants that can be cultivated because it has beautiful leaf patterns and has a fairly high/expensive price. The purpose of this research is to find out: (1) business prospects for aglaonema ornamental plants, (2) income of aglaonema ornamental plant farmers, and (3) what obstacles are faced by aglaonema farmers. The number of respondents in this study were 36 people using the case method. Based on the results of this study, the average income of aglaonema ornamental plant farmers in Mataram City is IDR 10,453,772/year with an average production cost incurred on aglaonema ornamental plant businesses in Mataram City amounting to IDR 39,230,000/year. The constraints faced by aglaonema ornamental plant farmers in the city of Mataram are: capital, marketing and plant propagation